Policy Network on Village Development in Bandung Regency (Study on Community-Based Housing and Settlement Development) - Entang Adhy Muhtar; Riswanda Riswanda (Universitas Sultan Ageng Tirtayasa, 2023)
Rural development, especially the construction of community-based housing and settlement areas in Bandung Regency in general, has not yet touched on the basic issue of increasing people's welfare through the development of integrated and sustainable residential areas. Development is still limited to physical improvements and institutional roles and involvement among stakeholders that are not yet integrated, both in planning, implementation, and regulatory support. This is related to the role of policy networks that have not been effective in the development of community-based housing and rural settlement areas in Bandung Regency. The research used a qualitative method, involving informants from various relevant stakeholders. The results of the study show that of the seven primary factors in the policy network, namely Actors, Functions, Structure, Institutionalization, Rules of Conduct, Power Relations, and Actor Strategies, although some tasks and programs have been relatively realized by local governments and non-governmental functional community participation already exists, it is not optimal, regulations and planning are not synchronized, financing is limited, and target results are not yet maximized, so it is not yet fully supportive (effective) in the construction of housing and residential areas in Bandung Regency.